In vitro biological activity of liposomal-containing antimony trioxide (Research, Society and Development, 2021)
Antimonials are used as chemotherapy for leishmaniasis, but have limited results due to their toxicity and broad resistance already acquired by the parasites. Nanotechnology offers an alternative to reduce these effects through the use of biocompatible nanocarriers, which can be vectorized to the target site. In addition, the redirection of molecules, already developed for the treatment of other pathologies, has the advantage of being already approved for therapy by regulatory agencies. The present study addresses the production of liposomal vesicles containing antimony trioxide (LC Sb2O3), as well as the evaluation of activity against tumor and bacterial cells. We produce liposomes in order of nanometric size, polydispersity index (PDI